Which genes to assess in the NGS diagnostics of intellectual disability? The case for a consensus database-driven and expert-curated approach. (June 2019) - Erger, Florian; Schaaf, Christian P.; Netzer, Christian
Abstract: When deciding on which genes to assess in larger Next-Generation Sequencing (NGS) datasets for the molecular genetic diagnosis of intellectual disability (ID), geneticists today have a variety of gene-phenotype databases and expert-curated gene lists available. To quantify their respective completeness, we compare an ID gene selection auto-generated from the Human Phenotype Ontology gene-phenotype association database and expert-curated ID gene lists from three reputable sources (sysID, the DDD consortium and Genomics England) and analyse some of their differences. We give examples of what we regard as genuine gaps ("missing ID genes") for each of these and conclude that a complementary or consensus approach is needed to maximise diagnostic yield in ID patients. We propose several consensus gene lists with ID-associated genes of different confidence levels. Highlights: Expert-curated gene databases for intellectual disability (ID) contain genuine gaps for well-established ID syndromes. Using any single source of ID-associated genes comes with a small, but avoidable risk of generating a false negative result. We propose consensus gene selections to maximise diagnostic yield and minimise unsolicited findings.